2018
DOI: 10.1186/s12986-018-0243-5
|View full text |Cite|
|
Sign up to set email alerts
|

The common use of improper control diets in diet-induced metabolic disease research confounds data interpretation: the fiber factor

Abstract: Diets used to induce metabolic disease are generally high in fat and refined carbohydrates and importantly, are usually made with refined, purified ingredients. However, researchers will often use a low fat grain-based (GB) diet containing unrefined ingredients as the control diet. Such a comparison between two completely different diet types makes it impossible to draw conclusions regarding the phenotypic differences driven by diet. While many compositional differences can account for this, one major differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
127
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(130 citation statements)
references
References 40 publications
(35 reference statements)
3
127
0
Order By: Relevance
“…More broadly, the overall composition of the so‐called control diets in animal studies is an important consideration with regard to their relevance when animals fed control diets are compared with animals fed specific diets. For instance, a recent study has shown that the fibre content may not be equal in control diets containing unrefined ingredients and in custom‐made “high fat” diets . This difference in fibre content, just like the difference of AGE content that we report here, may affect the metabolic disorders followed in animal studies.…”
Section: Discussionmentioning
confidence: 60%
“…More broadly, the overall composition of the so‐called control diets in animal studies is an important consideration with regard to their relevance when animals fed control diets are compared with animals fed specific diets. For instance, a recent study has shown that the fibre content may not be equal in control diets containing unrefined ingredients and in custom‐made “high fat” diets . This difference in fibre content, just like the difference of AGE content that we report here, may affect the metabolic disorders followed in animal studies.…”
Section: Discussionmentioning
confidence: 60%
“…As described in detail above, purified ingredient diets are very different from GB diets, and as one may expect, these differences can play a role in data interpretation when both are used in the same study. The problem with using a GB diet as a control diet for a high fat purified ingredient diet has been discussed and recent surveys suggest this problem still can be found in many studies (Fodde, Schmitt, Schewe, & Augenlicht, ; Pellizzon & Ricci, ; Rendina‐Ruedy & Smith, ; Warden & Fisler, ). In a recent survey of 69 publications including Cell , Nature , and Diabetes using search terms ‘mouse high fat’, it was found that only 18.8% of studies used a matched purified ingredient low fat control diet for the high fat diet while 40.6% used a GB diet as the low fat ‘control’ diet, with the remaining 40.6% of papers not providing sufficient data to determine what control diet was used (Pellizzon & Ricci, ).…”
Section: Choose the Control Diet With Carementioning
confidence: 99%
“…The problem with using a GB diet as a control diet for a high fat purified ingredient diet has been discussed and recent surveys suggest this problem still can be found in many studies (Fodde, Schmitt, Schewe, & Augenlicht, 2017;Pellizzon & Ricci, 2018;Rendina-Ruedy & Smith, 2016;Warden & Fisler, 2008). In a recent survey of 69 publications including Cell, Nature, and Diabetes using search terms 'mouse high fat', it was found that only 18.8% of studies used a matched purified ingredient low fat control diet for the high fat diet while 40.6% used a GB diet as the low fat 'control' diet, with the remaining 40.6% of papers not providing sufficient data to determine what control diet was used (Pellizzon & Ricci, 2018). A study by Chassaing et al (Chassaing et al, 2015) brought this issue to light when they used 3 different diets in their study: a GB diet (Purina 5001) and 2 purified ingredient diets, one with 10 kcal% fat and the other with 60 kcal% fat, both with cellulose as the only source of fiber.…”
Section: Of 14mentioning
confidence: 99%
“…363,367 Poor reporting of research-relevant diet factors such as differences between purified and natural ingredient diets have attracted attention and concern recently. 10, 358,368 Research diets are frequently provided ad libitum to rodents on shorter term studies. Diet restriction in long-term studies usually improves survival and reduces neoplastic, kidney, inflammatory, and other lesions.…”
Section: Crispr-cas9mentioning
confidence: 99%